Concentration and the value of D-dimer in the diagnosis of deep vein thrombosis - Van Nguyen-Thanh Phan; De Nhi Nguyen; Tri Dang-Minh Bui; Minh Duc Tong; Trung Hoang Nguyen; Dung Thi-Ngoc Nguyen (Revista Cubana de Medicina Militar)
Introduction: Quantification of D-dimer levels is a valuable test in orienting the diagnosis of deep vein thrombosis. Objectives: Determine D-dimer concentration and diagnostic value of D-dimer in patients with deep venous thrombosis. Methods: A descriptive, uncontrolled study was performed in 260 elderly patients at risk of deep vein thrombosis. All patients underwent quantitative D-dimer assay. Results: The D-dimer concentration of patients with deep venous thrombosis had a median of 3106.5 ng/ml and was about 1.5 times higher than that of patients without deep venous thrombosis. With a threshold of D-dimer concentration of 500 ng/mL to determine deep venous thrombosis, the specificity of the method is low (16.51%), but the sensitivity is high (100%). And the positive predictive value is low (18.75%) but the negative predictive value is absolute (100%). Conclusion: With a threshold of D-dimer concentration of 500 ng/mL to determine deep venous thrombosis, the specificity and positive predictive value of the method are low, but the sensitivity and negative predictive value are high.